EFFECT OF SOCIAL MEDIA ON BUYING INTEREST AND CONSUMER BUYING DECISIONS: A Systematic Literature Review - Arief Budiyanto; Ibrahim Bali Pamungkas; Alvin Praditya (Inovasi, 2022)
This study describes how the development of consumer behavior research on social media, the types of research and objects on buying interest and buying decisions on social media, and the determining factors that determine this. All of them are summarized through a systematic literature review of 73 journals that are used as references. In collecting journals, the researcher used the PICO approach to formulate research questions and the use of protocols in the process of inclusion and exclusion of research journals. It was found that the quantitative research approach still dominates research with that theme, the object of research on beauty and fashion, websites and e-commerce, food and beverages, and services, which are the most widely discussed themes in reference journals, while the determinant factors that determine consumer buying interest in the media are, among others, attention, interaction, and communication of members of social media, as well as ease of access. These factors also increase consumer buying interest on social media, while in purchasing decisions, informative factors, consumer social media usage behavior, and convenience are factors that influence consumer buying interest and purchasing decisions on media. social.Keywords:   Systematic Literature Review, SocialMedia, Online Buying Interest, Online Purchase Decisions, Online Consumer Behavior